Tempo dedicado ao trabalho: análise das decisões judiciais do Tribunal Trabalhista do Paraná sobre o trabalho remoto dos tutores eletrônicos no ensino a distância - Bodenmuller, Andreia Aline Nunes Machado (2021)
The objective of this study is to analyze how organizations, workers and the Paraná Labor Court (TRT/PR) define the time dedicated to the work of tutor teachers who work in the Distance Learning (EAD) modality from the perspective of Administration and Organizational Studies . Therefore, a research with a qualitative and descriptive character was developed, supported by the documentary research of judgments collected from the TRT/PR of actions filed by tutor professors in the face of the same educational institution. The analysis of secondary data adopted the technique of content analysis, by Bardin (2011). From the survey results, three categories emerged related to the temporal temporality of these professionals: working time, available time, working hours and availability without or with continuity. Technological tools, in the exercise of tutoring, suggest the false perception of autonomy and freedom for individual work organization, as control becomes more subtle and intense. The judgments show that flexible hours favor the invasion of working hours over non-work, só that the free distribution of the workload increases the appropriation and expansion of living time, reducing and canceling dead time and, consequently, resulting in plus absolute value (lengthening the journey) and plus relative value (reducing lost times).